2020
DOI: 10.1111/jpc.14703
|View full text |Cite
|
Sign up to set email alerts
|

Meconium aspiration syndrome: incidence, associated risk factors and outcome‐evidence from a multicentric study in low‐resource settings in Nepal

Abstract: Aim: The aim of this study was to identify the incidence, risk factors and outcome associated with meconium aspiration syndrome (MAS). . All babies born within the study period were included in the study. Babies who were diagnosed as MAS were designated as outcome. Data were analysed with bivariate analysis followed by multiple regression analysis. Results: The overall incidence of MAS was 2.0 per 1000 livebirths. Babies born at post-term gestation (adjusted odds ratio (AOR) = 2.41; 95% confidence interval (CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
1
8
0
1
Order By: Relevance
“…The incidence of MAS was high in Nepal with an overall incidence of about 2.0 per 1000 live births. 11 Studies conducted in Nepal have revealed the prevalence of MSAF about 6.5%-14.6%, 8 , 9 , 12 among all live deliveries, the prevalence of MAS among MSAF about 6.6% to 8.6%, 8 , 12 and neonatal mortality from MAS about 5.4% to 11.3%. 8 , 9 , 12 The study conducted in India found the prevalence of MAS among MSAF as 7.7% to 21.5%, 4 - 6 and mortality among MAS as high as 13.8%.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of MAS was high in Nepal with an overall incidence of about 2.0 per 1000 live births. 11 Studies conducted in Nepal have revealed the prevalence of MSAF about 6.5%-14.6%, 8 , 9 , 12 among all live deliveries, the prevalence of MAS among MSAF about 6.6% to 8.6%, 8 , 12 and neonatal mortality from MAS about 5.4% to 11.3%. 8 , 9 , 12 The study conducted in India found the prevalence of MAS among MSAF as 7.7% to 21.5%, 4 - 6 and mortality among MAS as high as 13.8%.…”
Section: Discussionmentioning
confidence: 99%
“…13 In the present study, there were 82 (41%) patients who had grade I MSL, 63 (31.5%) patient who had grade II MSL whereas 55 (27.5%) patients who had grade III MSL. Paudel P et al 14 studied incidence, associated risk factors and outcome evidence of meconium aspiration syndrome in Nepal. In their study, 11/122(9%) cases of MAS were among multiparous women, 78/122(63.9%) cases of MAS were among nulliparous women and 33/122(27%) cases of MAS were among primiparous women.…”
Section: Discussionmentioning
confidence: 99%
“…Su incidencia varía entre 0,4 y 4 por 1.000 nacidos vivos (1)(2)(3). En los países desarrollados ha disminuido en los últimos años a raíz del cambio de las prácticas obstétricas (4).…”
Section: Introductionunclassified